Recombinant Staphylococcal protein A with cysteine residue for preparation of affinity chromatography stationary phase and immunosensor applications - Gorbatiuk, O.B.; Bakhmachuk, A.O.; Dubey, L.V.; Usenko, M.O.; Irodov, D.M.; Okunev, O.V.; Kostenko, O.M.; Rachkov, A.E.; Kordium, V.A. (Вiopolymers and Cell, 2015)
Aim. Engineering of recombinant Staphylococcal protein A with cysteine residue (SPA-Cys) for preparation of affinity chromatography stationary phase and formation of bioselective element of immunosensor. Methods. DNA sequences encoding IgG-binding region of SPA, His-tag and cysteine were genetically fused and expressed in E. coli. SPA-Cys was immobilized on maleimide-functionalized silica beads for affinity chromatography stationary phase preparation and on a gold sensor surface as a bioselective element of immunosensor. Results. SPA-Cys was expressed at a high-level in a soluble form. The target protein was purified and showed a high IgG-binding activity. The capacity of the obtained SPA-Cys-based affinity chromatography stationary phase was 10–12 mg of IgG /ml. The purity of eluted IgG was more than 95 % in one-step purification procedure. The developed SPA-Cys-based bioselective element of immunosensor selectively interacted with human IgG and did not interact with the control proteins. Conclusions. The recombinant Staphylococcal protein A with cysteine residue was successfully used for the preparation of affinity chromatography stationary phase and formation of the bioselective element of immunosensor. Цель. Получение рекомбинантного белка А Staphylococcus aureus с остатком цистеина (SPA-Cys) и его применение для аффинной хроматографии и формирования биоселективного элемента иммуносенсора. Методы. Генно-инженерными методами конструировали и экспрессировали в E. coli последовательность ДНК, которая кодирует пять IgG-связывающих доменов SPA, His-таг и цистеин. Полученный рекомбинантный белок SPA-Cys иммобилизовали на малеимид-активированных микрогранулах силикагеля для приготовления биоафинного сорбента и на золотой сенсорной поверхности для разработки иммуносенсора. Результаты. Cинтезом в E. coli был получен белок SPA-Cys в растворимой форме с высоким выходом. Очищенный рекомбинантный белок А имеет высокую IgG-связывающую активность. Емкость синтезированного с использованием SPA-Cys биоафинного сорбента составляла 10–12 мг IgG/мл. Одностадийная процедура аффинной хроматографии сыворотки крови позволяет получать IgG с чистотой более 95 %. Показано, что биоселективный элемент иммуносенсора, сформированный на основе SPA-Cys, избирательно взаимодействует с IgG человека и не взаимодействует с контрольными белками. Выводы. Рекомбинантный белок SPA-Cys был успешно использован для приготовления стационарной фазы аффинной хроматографии и формирования биоселективного элемента иммуносенсора. Мета. Отримання рекомбінантного білка А Staphylococcus aureus із залишком цистеїну (SPA-Cys) та його застосування для афінної хроматографії та формування біоселективного елемента імуносенсора. Методи. Генно-інженерними методами конструювали та експресували в E. coli послідовність ДНК, яка кодує п’ять IgG-зв’язувальних доменів SPA, His-таг і цистеїн. Отриманий рекомбінантний білок SPA-Cys іммобілізували на малеїмід-активованих мікрогранулах силікагелю для приготування біоафінного сорбенту та на золотій сенсорній поверхні для розробки імуносенсора. Результати. Cинтезом у E. coli був отриманий білок SPA-Cys в розчинній формі з високим виходом. Очищений рекомбінантний білок А має високу IgG-зв’язувальну активність. Ємність біоафінного сорбенту з іммобілізованим SPA-Cys складала 10–12 мг IgG/мл. Одностадійна процедура афінної хроматографії сироватки крові дозволяє отримувати IgG з чистотою більш ніж 95 %. Показано, що біоселективний елемент імуносенсора, сформований на основі SPA-Cys, вибірково взаємодіє з IgG людини і не взаємодіє з контрольними білками. Висновки. Рекомбінантний білок SPA-Cys був успішно використаний для приготування стаціонарної фази афінної хроматографії і формування біоселективного елемента імуносенсора.